Strategy for implementing digitalization in the educational process as a factor in improving business process management and personnel management efficiency in higher education institutions - Soroka, Dmytro; Bikulov, Damir; Markova, Svitlana; Markov, Ivan (Management and Entrepreneurship: Trends of Development, 2024)
The article is to determine the process of digitalization of higher education, defines the main priorities in this area, and defines the tasks. It is emphasized that digitalization becomes an integral part of the development of all aspects of social life, including the educational system. The development of a digital higher education institution should be accompanied by monitoring the needs of the modern market, implementing and updating educational programs at all levels in accordance with the key competencies of digitization, as well as ensuring their continuity. Digitalization of society has a socio-cultural basis. The purpose of the study is to analyze trends in the development of digitization in modern higher educational institutions of Ukraine and EU countries, prospects for their interaction and mutual influence. The article uses the dialectical method, as well as instrumental and functional approaches. The authors came to the conclusion that in Ukraine, the process of development of digitization and digitalization of higher education is taking place gradually, but has positive dynamics. The authors provided recommendations on possible ways of developing the process. The results of the study are summarized in the following conclusions: digital technologies are a unique mechanism for the versatile development of a modern higher education institution. Thanks to digital technologies, we can confidently talk about the globalization of the scientific world and the active development of academic mobility. JEL Classification: C87, M10, M31, F02, F29